Ultrasound Diagnosis of Kidney Damage in Type 1 Diabetes Mellitus - Madaminkhuzhaeva D.K.; A.A.Sabyrov; Zulunov A.T (Zien Journals, 2023)
This article highlights the work on ultrasound diagnostics of kidney damage in type 1 diabetes mellitus.
Keywords: ultrasound; diabetes mellitus; echogenicity